Treatment outcomes of penetrating abdominal injury requiring laparotomy at Hiwot Fana Specialized University Hospital, Harar, Ethiopia - Abdulkadir, Adnan; Mohammed, Burka; Sertse, Elias; Mengesha, Melkamu Merid; Gebremichael, Mathewos Alemu (Frontiers in Surgery, 2022)
Abstract Background: Penetrating abdominal injury (PAI) is a public health problem and accounts for significant mortality and disability in both developing and developed countries. It often causes damage to internal organs resulting in shock and infection. In this study, we assessed the outcomes of PAI and factors associated with post-surgical outcomes including surgical site infection (SSI) and in hospital death. Methods: An institution-based cross-sectional study was conducted from January 15 to 30, 2020, using a standard checklist to review clinical charts of patients who presented to Hiwot Fana Specialized University Hospital (HFSUH) with the PAI and underwent laparotomy between January 2015 to September 2019. Descriptive statistics were used to describe the characteristics of patients and odds ratios (ORs) with a 95% confidence interval (CI) were reported for factors included in binary logistic regression. The statistical significance was declared at P-value < 0.05. Results: a total of 352 charts of patients with PAI were reviewed. Majority, 84.9% were males and mean age was 26.5 years. The anterior abdomen was the commonest site injured, 285(81%), and 329(93.5%) had organ injury, 204(62%) had a single organ injury, and 125(38%) had more than one organ injury. The leading injured organs were small intestines 194(55.1%), followed by colon 88(25%) and liver 40(11.4%). The magnitude of SSI and hospital death was 84(23.9%) and 12(3.4%), respectively. Patients having age above 45 years (AOR=2.9, 95%CI: 1.2, 9.2), fluid collection (AOR=2.7, 95%CI: 1.2, 5.9), colostomy (AOR=3.9, 95%CI: 1.9, 7.8), body temperature > 37.5 oc (AOR=3.8,95% CI:1.9,7.6), and Hgb < 10 mg/dl (AOR= 7.4, , 95%CI: 3.4,16.1) had higher likelihood of SSI. Those patients admitted to the intensive care unit (AOR = 21.3, 95%CI: 1.1, 412.3), and undergone damage control surgery (AOR = 9.6, 95%CI: 1.3, 73.3) had a higher likelihood of mortality rate. Conclusions: The SSI and death among patients with PAI was high. Age, fluid collection, colostomy, body temperature, and hemoglobin level were statistically associated with SSI, and intensive care unit and damage control surgery were statistically associated with death. Therefore, health professionals working in surgical wards should take these factors in the consideration to alleviate SSI.